Association between triglyceride-glucose index and phenotypic age acceleration: a cross-sectional study based on NHANES database - Zhao, Zhili; Liang, Yan (Frontiers in Physiology, 2025)
ObjectiveTo investigate the association between triglyceride-glucose (TyG) index and phenotypic age acceleration (PhenoAgeAccel), given the emerging importance of biological aging as a health determinant and the role of insulin resistance in aging-related processes.MethodsThis cross-sectional study analyzed data from 13,291 adults aged ≥20 years in the National Health and Nutrition Examination Survey (1999–2010). The TyG index served as the exposure variable, calculated from fasting triglycerides and glucose levels. PhenoAgeAccel, derived from clinical biomarkers, was the outcome variable. Analyses adjusted for demographic, socioeconomic, and health-related covariates.ResultsA significant non-linear relationship was observed between TyG index and PhenoAgeAccel, with an inflection point at 9.60. In the fully adjusted model, each unit increase in TyG index was associated with 2.21 years increase in PhenoAgeAccel (95% CI: 1.99, 2.43). The association was stronger above the inflection point (β = 8.21, 95% CI: 7.59, 8.82) compared to below it (β = 0.56, 95% CI: 0.29, 0.83).ConclusionHigher TyG index levels are significantly associated with accelerated biological aging, particularly above a threshold of 9.60. These findings suggest the importance of metabolic health in biological aging processes and potential interventional strategies.